2018
DOI: 10.1016/j.bbi.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential binding of antibodies in PANDAS patients to cholinergic interneurons in the striatum

Abstract: Pediatric Autoimmune Neuropsychiatric Disorder Associated with Streptococcus, or PANDAS, is a syndrome of acute childhood onset of obsessive-compulsive disorder and other neuropsychiatric symptoms in the aftermath of an infection with Group A beta-hemolytic Streptococcus (GABHS). Its pathophysiology remains unclear. PANDAS has been proposed to result from cross-reactivity of antibodies raised against GABHS with brain antigens, but the targets of these antibodies are unclear and may be heterogeneous. We develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
(78 reference statements)
4
31
0
Order By: Relevance
“…Elevation of CaMKII activity suggested that the autoantibodies have bioactivity, consistent with findings of autoimmunity and neuroinflammation in PANDAS and SC (27), including basal ganglia and/or dopamine receptor encephalitis (26,33). Additional studies are in progress to further investigate the validity of our conclusions, the presence of other neuronal autoantibodies (38), and better understand the pathogenetic mechanisms in disease.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Elevation of CaMKII activity suggested that the autoantibodies have bioactivity, consistent with findings of autoimmunity and neuroinflammation in PANDAS and SC (27), including basal ganglia and/or dopamine receptor encephalitis (26,33). Additional studies are in progress to further investigate the validity of our conclusions, the presence of other neuronal autoantibodies (38), and better understand the pathogenetic mechanisms in disease.…”
Section: Discussionsupporting
confidence: 79%
“…Expression of the chorea-derived human monoclonal antibody (mAb) 24.3.1 in transgenic mice led to autoantibody targeting of dopaminergic neurons in basal ganglia as well as additional neurons in the cerebral cortex (26). Further, anti-neuronal autoantibodies in sera of PANDAS patients have been shown to target cholinergic interneurons in mouse striatum (38). These interneurons depolarize spontaneously in a manner similar to the cardiac sinoatrial node and help to auto-regulate the local neuronal circuitries (39).…”
Section: Introductionmentioning
confidence: 99%
“…PANDAS patients exhibited significantly enlarged volumes of striatum in comparison to control groups, according to Giedd et al [62]. The binding of serum antibodies obtained from children diagnosed with PANDAS to cholinergic interneurons in the striatum of mice was significantly higher in comparison to control groups [64]. This finding may present one of the potential loci of the pathophysiology of PANDAS.…”
Section: Striatum and Striatal Interneuronsmentioning
confidence: 87%
“…Antibodies from children with PANDAS bound to ∼80% of cholinergic interneurons, significantly higher than the <50% binding seen with matched healthy controls. Remarkably, after treatment with IVIG, symptom improvement resolved in parallel with a reversal of the elevated binding of antibodies to cholinergic interneurons 40 . Individuals with TS have fewer cholinergic interneurons in their striatum, based on the examination of postmortem brain tissue 41 .…”
Section: Microglia and The Role Of The Immune System In Normal Brain mentioning
confidence: 94%